Recovery of Copper(II) and Silver(I) from Nitrate Leaching Solution of Industrial Dust via Solvent Extraction with LIX63 - Pan-Pan Sun; Tae-Young Kim; Hyeon Seo; Sung-Yong Cho (Metals, 2021)
A nitrate leachate containing Cu(II), Ag(I), Ni(II), Mg(II), and Al(III) was obtained during the leaching of industrial dust, which arises during the pyrometallurgy of spent camera modules. To separate and recover Cu(II) and Ag(I) from the leaching solution, solvent extraction experiments using 5,8-diethyl-7-hydroxydodecan-6-oxime (LIX63) were conducted. LIX63 was found to selectively extract Cu(II) and Ag(I) over other metal ions (Ni(II), Mg(II), and Al(III)) at low nitric acid concentrations. The extraction efficiency of Cu(II) was more affected than that of Ag(I) by the acidity of the feed solution and the LIX63 concentration in the organic phase. Cu(II) and Ag(I) were simultaneously extracted using 2 mol/L LIX63. Cu(II) was separated from the loaded LIX63 via stripping with 4 mol/L HNO3, whereas Ag(I) was recovered via stripping with 0.1 mol/L thiourea after the removal of Cu(II). McCabe–Thiele diagrams for the extraction and stripping of Cu(II) and Ag(I) were constructed. The complete extraction of Cu(II) and Ag(I) was confirmed via counter-current extraction. Moreover, stripping simulation tests confirmed that higher than 99.99% of Cu(II) and 99.2% of Ag(I) were stripped. The purities of Cu(II) and Ag(I) in the recovered solution were 95.2% and 99.993%, respectively. A process flow chart for the recovery of Cu(II) and Ag(I) from the nitrate leachate of the target industrial dust was also provided.